External Beam Radiation Therapy (EBRT) for Patients with Malignant Pheochromocytoma and Non-Head and Neck Paraganglioma: Combination with (131)I-MIBG - Fishbein, Lauren (Horm Metab Res, 2012)
In patients with malignant pheochromocytoma and paraganglioma, (131)I-MIBG radiotherapy can achieve an objective response rate of 30–50% with the dose limiting toxicity being hematologic. Patients with disseminated disease, who also have a few index bulky or symptomatic lesions, may benefit from the addition of targeted external beam radiotherapy alone or in combination with systemic (131)I-MIBG. The records of patients with malignant paraganglioma who were treated with external beam radiotherapy at the University of Pennsylvania from February 1973 to February 2011 were reviewed in an institutional review board approved retrospective study. Of the 17 patients with tumors in the thorax, abdomen, or pelvis, 76% had local control or clinically significant symptomatic relief for at least one year or until death. As expected, the predominant toxicity was due to irradiation of tumor-adjacent normal tissues without clinically significant hematologic toxicity. Due to widespread systemic metastases with areas of bulky, symptomatic tumor, five of the 17 patients were treated with sequential (131)I-MIBG (2 mCi/kg per treatment) and external beam radiotherapy to nine sites. In these patients, all areas that were irradiated with external beam radiotherapy showed durable objective response despite all patients eventually experiencing out-of-field systemic progression requiring other treatment. Four of these patients remain alive with excellent performance status 16, 18, 23, and 24 months after external beam radiotherapy. External beam radiotherapy can be highly effective in local management of malignant paraganglioma and can be used in conjunction with (131)I-MIBG due to non-overlapping toxicities with excellent control of locally bulky tumors.